Quod bonum felix faustumque sit. Ehrenpromotion von Walter Jens zum Dr. theol. h. c. am 3. Juni 2005 in der Universität Hamburg - Dierken, Jörg; Timm, Stefan (Hamburger Universitätsreden Neue Folge, 2006)
This volume documents speeches and speeches given on the occasion of the award of the Dr. theol. honoris causa by the Department of Protestant Theology to Professor Dr. mult. Walter Jens have been held on June 3, 2005.